Care of injured during disasters - Pawłowski, Witold; Goniewicz, Krzysztof; Goniewicz, Mariusz; Czerski, Robert; Lasota, Dorota (Journal of Education, Health and Sport, 2018)
Disasters are very big challenge for health services around the world. The media almost daily inform mass accidents or disasters. In Poland, the issue of responding to events mass rests largely on the State Emergency Medical System. The paper presents the activities carried out by emergency medical services on health in emergency situations. The paper characterized conducting rescue operations and the problems and errors occurring during the conduct of rescue operations.